Organizational and methodical system of formation of aesthetic culture of the future teachers of fine arts in Pedagogical University - Sotska, Galyna (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the problem of the formation of aesthetic culture artists future teachers in pedagogical universities. The essence of organizational and technical system of formation of aesthetic culture of the future teachers of the fine arts, which is an ordered set of interrelated and interdependent elements that constitute the holistic education that has integrated features and is subject to contributing to the establishment of aesthetic culture of the future teachers of the fine arts. Author determined there are structural and functional components, such as: goal, objectives, approaches (axiological, cultural, activity, integration, competence) and principles (methodological, psychological, artistic, educational, methodical ) of its operation, corresponding motivational functional components; content of the educational process (content- projecting functional component that includes artistic and pedagogical training (theoretical, practical, independent) and activities (aesthetic, educational, artistic, educational, artistic, aesthetic, aesthetic and ecological, Extracurricular, artistic and aesthetic); organizational forms and methods of implementation (traditional and non-traditional, interactive, artistic, educational, artistic and aesthetic (organizational function and activity component), teaching conditions and teaching support, which leads to the effective functioning of the system (correction – functional regulatory component), teaching result, ie the level of formation of aesthetic culture of students achieved as a result of organizational and technical system (control and effective functional component).